The Role of Financial Literacy in Mediating Overconfidence, Representativeness, Anchoring, and Availability Bias on Investment Decisions - Viana Khoerunnisa; Ika Yustina Rahmawati; Naelati Tubastuvi; Alfato Yusnar Kharismasyah (MEC-J (Management and Economics Journal), 2026)
This study aimed to investigate the relationship between heuristic behavioral biases and investment decision-making among Generation Z in Banyumas Regency, based on Behavioral Finance Theory and Heuristic Behaviour Theory, using financial literacy as a mediator in the decision-making process. The methods used in this study are quantitative, employing purposive sampling techniques with data from Generation Z in Banyumas who invest in financial and real assets, comprising 282 respondents aged 18-29 years. Data were collected via a questionnaire and analyzed using the SmartPLS method to test the relationship among variables in the research model, as measured through questionnaire indicators. The results showed that availability has a significant positive direct effect on investment decisions; overconfidence and availability have significant positive effects mediated by financial literacy; whereas representativeness does not have a significant effect on investment decisions, either directly or indirectly. A key finding of this study is that financial literacy partially mediates heuristic behavior regarding investment decisions. The results of this study indicated that the higher a person’s financial literacy, the more rational they will be in making investment decisions to achieve returns on their investments.